Peningkatan Kualitas Sumber Daya Manusia di Lingkungan Perguruan Tinggi melalui Pelatihan Penulisan Akademik dan Pengelolaan Open Journal System di STAI Yasba Kalianda : Pengabdian Masyarakat - Lukman Nuzul Hakim; Susilawati; Umar Sanusi; Lela Qomariah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The quality of human resources in the academic world highly depends on the ability to write scientific papers and professionally manage academic journals. At STAI Yasba Kalianda, academic writing skills and Open Journal System (OJS) management remain challenging. Therefore, this community service activity aims to provide training in academic writing and OJS management to improve the quality of scientific publications at STAI Yasba Kalianda. The implementation method includes lectures, interactive discussions, and hands-on practice on OJS usage. Evaluation was conducted through pre-test and post-test using the Moodle application in the form of an online quiz to measure participants' comprehension improvement. The results of this activity indicate a 40% increase in understanding, demonstrating that the training effectively enhances the academic capacity of participants. Through this training, it is expected that students and lecturers of STAI Yasba Kalianda will become more active in writing and managing academic journals professionally.